Social work practice in addiction rehabilitation: erenköy bahar model - Şamar, Berhudan; Buz, Sema (Journal of Dependence, 2022)
The increase in the number of alcohol and substance users and the fact that this situation has become a global problem has led to a greater focus on the detoxification and rehabilitation processes of individuals with alcohol and substance use disorder, as well as protective and preventive policies. The aim of rehabilitation in addiction treatment is to provide interventions and practices in a holistic way that will enable individuals with a diagnosis of alcohol and substance use disorder to cope with the medical, psychological, social, economic and legal problems caused by addiction. This study focuses on the social work practices in Erenköy Bağımlı Hastalar İçin Rehabilitasyon (BAHAR) Center, which offers individualized and holistic treatment for addicts in Turkey. Social workers in the center are actively engaged in activities of mending disrupted family relationships, offering functional social support mechanisms and post-rehabilitation planning with the aim to help addicted patients regain their psycho-social health back and stay clear of alcohol and substance. In this context, social work practices at Erenköy BAHAR Center begin with preparing social study reports, followed by family interviews, psychoeducation groups, social aid guidance, counseling, house visits and shelter counseling. It is considered important to increase the number of addiction rehabilitation centers and employ more social workers in the field to help addicted patients maintain their well-being and regain their social functionality.